Pengembangan Game Petualang untuk Pembelajaran Berhitung - Indah Rahmawati; Ibut Priono Leksono; Harwanto (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
his study developed a learning media in the form of games that were applied to devices using the Android system. During this time children eliminate boredom with games. Therefore, learning media in the form of games are developed so that students can take advantage of free time with something useful. This research aims to provide adventurous game learning media that have been validated by material experts, media experts and design expert as a support for numeracy learning. The method in this research use the Research and Development (P&P) method. This study produces form adventurous games for numeracy learning that are equipped with user manuals can be obtained at Playstore, Material expert validation is 84,76%, Media and design expert validation is 91,82%. Questionnaire responses of students to the adventurous game for learning to count reached very good criteria.